The Judge's Understanding of Iwad (Living Hadith in Palembang Religious Court) - Fatroyah Asr Himsyah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
This study aims to understand the perception of the Palembang Religious Court Judges about Iwad Khulu 'which originated from the Hadith. The results of this study indicate that there are two typologies of understanding of Iwad Khulu', both of theme are textual understanding and contextual understanding. According to the understanding of textual type, iwad must be understood to arise as a result of khulu 'because the husband violated the ta'lik talak so that the wife filed for divorce by paying a ransom in the form of money in the amount of ten thousand rupiahs according to the provisions in The PMA Number 2 of 1990 concerning Obligations of Marriage Registrar, through regulations this Judge no longer takes other considerations. Whereas the contextual type understands that Iwad Khulu 'depends on the type of khulu',when it khulu' due to violations of the ta'lik talak, the iwad depends on the provisions of the Ministry of Religion, while the khulu' purely caused by a reason other than the violation of the ta'lik talak then the considerations are proof, wife's ability and the principle of justice.